Liberalization of the Postal Service Market in Europe: Entry with Universal Service and Partial Coverage - Patrick Frank Ernst Beschorner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In the advent of postal market liberalization in several European countries we expect that the incumbent operators anticipate entry by competitors who are not required to offer universal service, i.e. coverage of the entire country and uniform pricing. The market for postal service exhibits stronger network effects than in telecommunications because of limited interconnection. In the present paper we model entrants which can opt for a partial geographical coverage and who enter with a higher service quality than the incumbent. This allows to predict possible deterrence or accommodating strategies by the incumbent. We show that dependent on the shape of the network costs and the network effects entrants may either offer a low quality in order to mitigate competition or offer a higher quality in order to restrict the entrant's geographical coverage.
Keywords: L51; L41; L12; 330; regulation; liberalization; postal services; Postbeförderung; Postdienst; Deregulierung; Markteintritt; Potenzieller Wettbewerb; Dienstleistungsqualität; Universaldienst; Produktdifferenzierung; Theorie; EU-Staaten